Method for preparing catalyst material based on sol-gel method
The cerium-based NH3-SCR catalyst material was synthesized by the sol-gel method, and the macroporous and mesoporous structures were introduced using polymer templates, which solved the problem of insufficient activity of the existing catalyst, achieved significant improvement in specific surface area and active sites, and significantly improved the performance of the catalyst.
Patent Information
- Application Number
- CN202411501574.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-10-25
AI Technical Summary
The existing cerium-based NH3-SCR catalysts have problems such as uncontrollable pore size and insufficient catalytic activity, making it difficult to develop efficient, highly selective and stable catalyst materials.
The sol-gel method was used to synthesize cerium-based NH3-SCR catalyst materials using polymethyl methacrylate and polyethylene oxide-polypropylene oxide-polyethylene oxide as pore templates, and large pore and mesoporous structures were introduced to improve the specific surface area and acidic sites of the catalyst.
The activity of the catalyst was significantly improved, the problems of low specific surface area and insufficient catalytic activity were solved, and significant technical effects were shown in the increase of active sites, enhanced adsorption effect, future application prospects and significant improvements in performance.
Smart Images

Figure CN119588333A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of exhaust gas post-treatment catalytic materials, and in particular to a method for preparing a catalyst material based on a sol-gel method. Background Art
[0003] Current research shows that the most effective way to degrade NOx is selective catalytic reduction (SCR), which generally uses NH3 as a reducing agent. SCR technology has the advantages of high efficiency, low reaction temperature and no secondary pollution, and its core is the selective catalytic reduction catalyst. One of the main technical difficulties is how to develop catalyst materials with high catalytic efficiency, strong selectivity, good stability, simple preparation, safety and lower cost.
[0004] Among them, NH3-SCR catalysts with three-dimensional porous structures have a wide range of application prospects because they have a unique porous framework and abundant Bronsted acid sites, which not only greatly enhance the reaction area, but also improve the denitrification activity. Cerium-based catalysts are a common NH3-SCR catalyst, and the most common load is titanium dioxide (TiO2). However, the current mainstream cerium-based catalysts have problems such as uncontrollable pore size and insufficient catalytic activity.
[0005] Currently, no effective solution has been proposed for the problems in the related technologies. Summary of the invention
[0006] In view of this, the present invention provides a method for preparing a catalyst material based on a sol-gel method to solve the above-mentioned problems.
[0007] In order to solve the above problems, the specific technical solutions adopted by the present invention are as follows:
[0008] A method for preparing a catalyst material based on a sol-gel method, the method comprising the following steps:
[0009] S10, dissolving methyl methacrylate in deionized water under an inert gas to obtain a methyl methacrylate solution;
[0010] S20, using the persulfate solution as an initiator to undergo a polymerization reaction with the methyl methacrylate solution to obtain a polymethyl methacrylate microsphere mother solution;
[0011] S30, diluting, centrifuging and drying the polymethyl methacrylate microsphere mother solution to obtain a polymethyl methacrylate template;
[0012] S40, dissolving deionized water and polyethylene oxide-polypropylene oxide-polyethylene oxide in anhydrous ethanol, stirring and mixing, and then adding cerium salt to obtain solution A;
[0013] S50, adding glacial acetic acid to the titanate, and mixing by stirring to obtain a solution B;
[0014] S60, adjusting the pH of solution A, and adding solution B dropwise into solution A, and mixing by stirring to obtain gel C;
[0015] S70, heat-treating the polymethyl methacrylate template, and dropping the gel C on the polymethyl methacrylate template, and obtaining a catalyst material by vacuum filtration, drying and calcining.
[0016] Preferably, dissolving methyl methacrylate in deionized water under an inert gas to obtain a methyl methacrylate solution comprises the following steps:
[0017] S101, introducing an inert gas into a four-necked flask filled with deionized water;
[0018] S102, placing the four-necked flask in an oil bath for heating and stirring;
[0019] S103, adding methyl methacrylate into uniformly stirred deionized water, and dissolving by stirring to obtain a methyl methacrylate solution.
[0020] Preferably, the process of using a persulfate solution as an initiator and polymerizing it with a methyl methacrylate solution to obtain a polymethyl methacrylate microsphere mother solution comprises the following steps:
[0021] S201, dissolving persulfate in deionized water, stirring and mixing to obtain a persulfate solution, and using the solution as an initiator;
[0022] S202, adding an initiator to the methyl methacrylate solution to obtain a polymethyl methacrylate microsphere mother solution through a polymerization reaction.
[0023] Preferably, the persulfate includes at least one of ammonium persulfate, sodium persulfate and potassium persulfate.
[0024] Preferably, diluting, centrifuging and drying the polymethyl methacrylate microsphere mother solution to obtain the polymethyl methacrylate template comprises the following steps:
[0025] S301, adding the polymethyl methacrylate microsphere mother solution into deionized water according to a preset volume ratio for dilution treatment;
[0026] S302, centrifugally filtering the diluted polymethyl methacrylate microsphere mother solution;
[0027] S303, placing the polymethyl methacrylate microsphere mother liquid after the centrifugal filtration treatment in an oven for drying treatment to obtain a polymethyl methacrylate template with a blue luster.
[0028] Preferably, deionized water and polyethylene oxide-polypropylene oxide-polyethylene oxide are dissolved in anhydrous ethanol, and cerium salt is added after stirring and mixing to obtain solution A, which comprises the following steps:
[0029] S401, uniformly mixing deionized water and polyethylene oxide-polypropylene oxide-polyethylene oxide according to a preset mass ratio to obtain a mixed reagent;
[0030] S402, adding the mixed reagent to anhydrous ethanol and performing magnetic stirring under heating in a water bath until the polyethylene oxide-polypropylene oxide-polyethylene oxide is dissolved to obtain a dissolved solution;
[0031] S403, adding cerium salt to the dissolved solution and mixing by stirring to obtain solution A.
[0032] Preferably, the cerium salt includes at least one of cerium nitrate, cerium chloride, cerium sulfate and cerium acetate.
[0033] Preferably, the titanate includes at least one of tetrabutyl titanate, tetraethyl titanate and tetraisopropyl titanate.
[0034] Preferably, adjusting the pH of solution A, and adding solution B dropwise to solution A, and stirring and mixing to obtain gel C comprises the following steps:
[0035] S601, adding nitric acid dropwise to solution A to adjust the pH of solution A to a range of 1-2;
[0036] S602, adding solution B dropwise to solution A with adjusted pH, and mixing by stirring to obtain gel C.
[0037] Preferably, the polymethyl methacrylate template is heat-treated, and the gel C is dripped onto the polymethyl methacrylate template, and the catalyst material is obtained by vacuum filtration, drying and calcining, which comprises the following steps:
[0038] S701, adding gel C dropwise to the heat-treated polymethyl methacrylate template; and performing vacuum filtration treatment;
[0039] S702, performing vacuum filtration and preliminary drying treatment on the polymethyl methacrylate template after the gel C is added;
[0040] S703, performing secondary drying on the polymethyl methacrylate template that has been subjected to several vacuum filtration and preliminary drying treatments;
[0041] S704, sending the polymethyl methacrylate template after secondary drying into a muffle furnace for calcination to obtain a catalyst material.
[0042] The beneficial effects of the present invention are:
[0043] The present invention utilizes polymethyl methacrylate and polyethylene oxide-polypropylene oxide-polyethylene oxide as pore templates, uses a gel sol method to synthesize a cerium-based NH3-SCR catalyst material, and introduces macropores and mesoporous structures, which significantly increase the specific surface area and acid sites of the catalytic material, thereby improving the activity of the catalyst, solving the problems of low specific surface area and insufficient catalytic activity of the NH3-SCR catalyst material, and exhibiting significant technical effects in terms of increased active sites, enhanced adsorption effect, future application prospects and significantly improved performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work. In the drawings:
[0045] Figure 1 is a flow chart of a method for preparing a catalyst material based on a sol-gel method according to an embodiment of the present invention;
[0046] Figure 2 is an exemplary schematic diagram of a method for preparing a catalyst material based on a sol-gel method according to an embodiment of the present invention;
[0047] Figure 3 is a SEM image of the material in Example 1 of a method for preparing a catalyst material based on a sol-gel method according to an embodiment of the present invention;
[0048] Figure 4 It is a schematic diagram of the NO conversion rate variation with temperature of the material of Example 1 and the material of Comparative Example 1 in a method for preparing a catalyst material based on a sol-gel method according to an embodiment of the present invention. DETAILED DESCRIPTION
[0049] In order to enable those skilled in the art to better understand the technical solutions in this application, the technical solutions in the embodiments of this application will be clearly and completely described below in conjunction with the drawings in the embodiments of this application. Obviously, the described embodiments are only part of the embodiments of this application, not all of the embodiments. Based on the embodiments in this application, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of this application.
[0050] According to an embodiment of the present invention, a method for preparing a catalyst material based on a sol-gel method is provided.
[0051] The present invention will now be further described with reference to the accompanying drawings and specific embodiments. Figure 1-2 and Figure 4 As shown, according to the method for preparing a catalyst material based on a sol-gel method according to an embodiment of the present invention, the method comprises the following steps:
[0052] S10, dissolving methyl methacrylate in deionized water under an inert gas to obtain a methyl methacrylate solution;
[0053] Specifically, dissolving methyl methacrylate in deionized water under an inert gas to obtain a methyl methacrylate solution comprises the following steps:
[0054] S101, introducing inert gas into a four-mouth flask filled with deionized water;
[0055] S102, placing the four-necked flask in an oil bath for heating and stirring;
[0056] The four-necked flask was placed in an oil bath for heating and stirring. The oil bath temperature was 80° C. and the stirring speed was 320 r / min-380 r / min.
[0057] S103, adding methyl methacrylate into uniformly stirred deionized water, and dissolving by stirring to obtain a methyl methacrylate solution.
[0058] Wherein, the volume ratio of methyl methacrylate to deionized water is 1:10.
[0059] It should be noted that an inert gas is introduced into the two end ports of the four-necked flask at a flow rate of 60 mL / min-70 mL / min to maintain an inert environment. A certain amount of deionized water is placed in the four-necked flask, and a thermometer is inserted into the front port to detect the temperature of the solution in the four-necked flask. One port is reserved for slowly adding methyl methacrylate during the oil bath stirring process.
[0060] S20, using the persulfate solution as an initiator to undergo a polymerization reaction with the methyl methacrylate solution to obtain a polymethyl methacrylate microsphere mother solution;
[0061] Specifically, the persulfate solution is used as an initiator and undergoes a polymerization reaction with a methyl methacrylate solution to obtain a polymethyl methacrylate microsphere mother solution, which includes the following steps:
[0062] S201, dissolving persulfate in deionized water, stirring and mixing to obtain a persulfate solution, and using the solution as an initiator;
[0063] It should be noted that the concentration of the persulfate solution is 0.005 g / mL-0.008 g / mL.
[0064] S202, adding an initiator to the methyl methacrylate solution to obtain a polymethyl methacrylate microsphere mother solution through a polymerization reaction.
[0065] It should be noted that the volume ratio of the persulfate solution to the methyl methacrylate solution is 1:(8-12), and the polymerization reaction time is 2-3 hours.
[0066] S30, diluting, centrifuging and drying the polymethyl methacrylate microsphere mother solution to obtain a polymethyl methacrylate template;
[0067] Specifically, the polymethyl methacrylate microsphere mother solution is diluted, centrifuged and dried to obtain the polymethyl methacrylate template, which includes the following steps:
[0068] S301, adding the polymethyl methacrylate microsphere mother solution into deionized water according to a preset volume ratio for dilution treatment;
[0069] S302, centrifugally filtering the diluted polymethyl methacrylate microsphere mother solution;
[0070] S303, placing the polymethyl methacrylate microsphere mother liquid after the centrifugal filtration treatment in an oven for drying treatment to obtain a polymethyl methacrylate template with a blue luster.
[0071] Specifically, the polymethyl methacrylate microsphere mother liquor is diluted into deionized water at a volume ratio of 1:3-1:4, and then centrifuged at a speed of 1800r / min-2500r / min, and then dried at 50°C to obtain a polymethyl methacrylate template with a blue-purple luster.
[0072] The volume ratio of the polymethyl methacrylate microsphere mother liquid to deionized water is 1:(2-3), and the polymethyl methacrylate microsphere mother liquid after centrifugal filtration is placed in an oven for drying for 2 hours to 3 hours.
[0073] S40, dissolving deionized water and polyethylene oxide-polypropylene oxide-polyethylene oxide in anhydrous ethanol, stirring and mixing, and then adding cerium salt to obtain solution A;
[0074] Specifically, deionized water and polyethylene oxide-polypropylene oxide-polyethylene oxide are dissolved in anhydrous ethanol, and cerium salt is added after stirring and mixing to obtain solution A, which includes the following steps:
[0075] S401, uniformly mixing deionized water and polyethylene oxide-polypropylene oxide-polyethylene oxide according to a preset mass ratio to obtain a mixed reagent;
[0076] It should be noted that the preset mass ratio of deionized water to polyethylene oxide-polypropylene oxide-polyethylene oxide is 1:(2-3).
[0077] S402, adding the mixed reagent to anhydrous ethanol and performing magnetic stirring under heating in a water bath until the polyethylene oxide-polypropylene oxide-polyethylene oxide is dissolved to obtain a dissolved solution;
[0078] It should be noted that the mass ratio of polyethylene oxide-polypropylene oxide-polyethylene oxide to anhydrous ethanol is 1:(5-6).
[0079] S403, adding cerium salt to the dissolved solution and mixing by stirring to obtain solution A.
[0080] The cerium salt includes at least one of cerium nitrate, cerium chloride, cerium sulfate and cerium acetate.
[0081] S50, adding glacial acetic acid to the titanate, and mixing by stirring to obtain a solution B;
[0082] The titanate includes at least one of tetrabutyl titanate, tetraethyl titanate and tetraisopropyl titanate. The molar ratio of glacial acetic acid to titanate is 1:(3-5), and the molar ratio of cerium salt to titanate is 1:(2-4).
[0083] S60, adjusting the pH of solution A, and adding solution B dropwise to solution A, and mixing by stirring to obtain gel C;
[0084] Specifically, adjusting the pH of solution A, and adding solution B dropwise into solution A, and stirring and mixing to obtain gel C comprises the following steps:
[0085] S601, adding nitric acid dropwise to solution A to adjust the pH of solution A to a range of 1-2;
[0086] S602, adding solution B dropwise to solution A with adjusted pH, and mixing by stirring to obtain gel C.
[0087] Solution B was added dropwise to solution A after pH adjustment, and a clear yellow gel C was obtained after vigorous stirring for 5-8 hours.
[0088] S70, heat-treating the polymethyl methacrylate template, and dropping the gel C on the polymethyl methacrylate template, and obtaining a catalyst material by vacuum filtration, drying and calcining.
[0089] Specifically, the polymethyl methacrylate template is heat-treated, and the gel C is dripped onto the polymethyl methacrylate template, and the catalyst material is obtained by vacuum filtration, drying and calcining, which comprises the following steps:
[0090] S701, adding gel C dropwise to the heat-treated polymethyl methacrylate template; and performing vacuum filtration treatment;
[0091] It should be noted that the heat treatment temperature of the polymethyl methacrylate template is 120° C. and the treatment time is 10 minutes.
[0092] S702, performing vacuum filtration and preliminary drying treatment on the polymethyl methacrylate template after the gel C is added;
[0093] S703, performing secondary drying on the polymethyl methacrylate template that has been subjected to several vacuum filtration and preliminary drying treatments;
[0094] S704, sending the polymethyl methacrylate template after secondary drying into a muffle furnace for calcination to obtain a catalyst material.
[0095] Specifically, the steps of dropping gel C on the heat-treated polymethyl methacrylate template for suction filtration, drying and calcining to obtain the NH3-SCR catalyst material include: heat-treating the obtained polymethyl methacrylate template, then dropping gel C on the surface of the polymethyl methacrylate template for vacuum filtration, and then drying for a short time; repeating the filtration and drying process twice; after completion, drying for a long time again. Finally, the sample is sent to a muffle furnace for calcination to obtain the final catalyst material.
[0096] It should be noted that the temperature for short-time drying is 40° C. and the drying time is 2 hours; the temperature for long-time drying after two filtrations and short-time drying is 60° C. and the drying time is 24 hours.
[0097] The sample was sent to a muffle furnace for calcination and heated to 280°C at a heating rate of 1°C / min, and then kept for 2 hours; then heated to 500°C at the same heating rate, kept for 4 hours, and naturally cooled to room temperature to obtain the NH3-SCR catalyst material.
[0098] Embodiment 1;
[0099] After the reaction temperature reached 200 mL of deionized water in a 500 mL four-necked flask, the nitrogen flow rate was set to 70 mL / min, the oil bath temperature was 85°C, and the stirring speed was 350 r / min. After the reaction temperature reached 20 mL of methyl methacrylate (MMA), stirring was continued for 20 minutes.
[0100] 0.1 g of sodium persulfate was dissolved in 20 mL of deionized water to obtain a sodium persulfate solution.
[0101] Sodium persulfate solution is used as an initiator and added into methyl methacrylate solution to cause a polymerization reaction. After two hours of reaction, a mother solution of polymethyl methacrylate microspheres is obtained.
[0102] The polymethyl methacrylate microsphere stock solution and deionized water were diluted in a volume ratio of 1:4.
[0103] The diluted polymethyl methacrylate microsphere mother liquid was placed in a centrifuge and centrifuged at a speed of 2000 r / min for 20 minutes.
[0104] The polymethyl methacrylate microspheres after centrifugation were placed in an oven and dried at 50° C. for 12 hours to obtain a polymethyl methacrylate template with a blue-purple luster.
[0105] 3 g of deionized water and 7 g of polyethylene oxide-polypropylene oxide-polyethylene oxide were uniformly mixed.
[0106] The mixed reagents were added to 40 g of anhydrous ethanol and magnetically stirred at 40° C. for 4 hours until the polyethylene oxide-polypropylene oxide-polyethylene oxide was completely dissolved.
[0107] After the polyethylene oxide-polypropylene oxide-polyethylene oxide is completely dissolved, 3.2 g of cerium acetate is added and stirring is continued for 30 minutes. This is recorded as solution A.
[0108] 0.8 g of glacial acetic acid was added dropwise to 10.2 g of tetrabutyl titanate, and the mixture was stirred magnetically for 30 min. This was recorded as solution B.
[0109] Nitric acid was added dropwise to solution A to adjust the pH to the range of 1-2, and then solution B was added dropwise. After vigorous stirring for 6 hours, a clear yellow gel C was formed.
[0110] The polymethyl methacrylate template was heat treated at 120 °C for 10 min.
[0111] Gel C was dropped onto a polymethyl methacrylate template and vacuum filtered.
[0112] After vacuum filtration, gel C was dried at 40°C for two hours, and the above filtration and drying process was repeated for gel C once more.
[0113] The obtained sol was placed in an oven and dried at 60° C. for 24 hours to obtain a gel sample.
[0114] The obtained gel sample was placed in a muffle furnace, heated to 280°C at a heating rate of 1°C / min, kept warm for two hours, and then heated to 500°C at the same heating rate, kept warm for four hours. After that, it was cooled to room temperature to obtain a catalyst material, which was a high-performance three-dimensional ordered macroporous-mesoporous NH3-SCR catalyst material.
[0115] Among them, the three-dimensional ordered macroporous-mesoporous cerium-based NH3-SCR catalyst can overcome the problems of high toxicity, poor stability, and insufficient activity of the current mainstream ammonia selective catalyst. However, the use of polymer templates to modify the catalyst structure during synthesis also has the problems of complex process and limited effect, and cost control and large-scale production are also challenges.
[0116] In view of the challenges from the material body and the preparation process, the present invention uses a soap-free emulsion polymerization method to synthesize a polymethyl methacrylate template, and when using a sol-gel method to synthesize a CeTiOx catalyst (a commonly used NH3-SCR catalyst group, also known as a cerium-based catalyst group), a polymethyl methacrylate template and a polyethylene oxide-polypropylene oxide-polyethylene oxide template are used to form different pore structures in the catalyst material, thereby preparing a high-performance three-dimensional ordered macroporous-structure catalyst material. The catalyst material prepared by the preparation method has excellent selectivity, high activity, and controllable nanostructure.
[0117] The morphology and structure of the catalyst affect the specific surface area, the dispersion of active components and the density of active sites. The macropores in the material can efficiently transfer mass, while the mesopores can increase the specific surface area to improve the utilization efficiency of the catalyst. In previous studies, three-dimensional ordered macroporous-mesoporous materials combining these two different pores have been widely studied. For example, a vanadium-based catalyst with a three-dimensional ordered macroporous-mesoporous structure has been shown to have higher catalytic activity and smoke resistance over a wider temperature range than traditional vanadium-based catalysts. Compared with vanadium-based catalysts, cerium-based catalysts have certain advantages in oxygen storage and release capacity, thermal stability, multifunctional active sites, and environmental friendliness. In this case, synthesizing a cerium-based catalyst with a three-dimensional ordered macroporous-mesoporous structure is a very promising research direction. The present invention designs a cerium-based NH3-SCR catalyst material with a three-dimensional ordered macroporous-mesoporous structure by using polymethyl methacrylate, polyethylene oxide-polypropylene oxide-polyethylene oxide as templates.
[0118] Comparative Example 1;
[0119] No polymethyl methacrylate template was prepared, and polyethylene oxide-polypropylene oxide-polyethylene oxide was not added when preparing solution A, and other steps were the same (using a common catalyst preparation method, and not using two organic templates to produce an ordered porous structure).
[0120] Test example;
[0121] Example 1 and Comparative Example 1 were tested, specifically:
[0122] The morphology of the products prepared in various embodiments of the present invention was observed using a fully automatic specific surface analyzer (model: ASAP2020HD88). The measured specific surface areas are shown in Table 1 and Table 2. Figure 3 The specific surface area of the product of Example 1 is shown (107.1 m2 / g).
[0123] The morphology of the products prepared in various embodiments of the present invention was observed using a scanning electron microscope (model: JSM-6700F), and the average pore size measured is shown in Table 1, and Figure 3 The average pore size of the product of Example 1 is (8.1 nm).
[0124] Table 1 Example test results
[0125] Test samples Specific surface area Average pore size Example 1 107.1 8.1 Comparative Example 1 48.7 7.5
[0126] In summary, with the help of the above-mentioned technical scheme of the present invention, the present invention uses polymethyl methacrylate and polyethylene oxide-polypropylene oxide-polyethylene oxide as pore templates, uses a gel sol method to synthesize a cerium-based NH3-SCR catalyst material, and introduces macropores and mesoporous structures, which significantly improves the specific surface area and acid sites of the catalytic material, thereby improving the activity of the catalyst, solving the problems of low specific surface area and insufficient catalytic activity of the NH3-SCR catalyst material, and showing significant technical effects in terms of increased active sites, enhanced adsorption effect, future application prospects and significantly improved performance.
[0127] Among them, the active sites are increased: compared with the prior art, the specific surface area of the present invention is significantly improved, the active sites on the catalyst surface are increased, and thus the catalytic activity of the catalyst is improved;
[0128] Enhanced adsorption effect: Compared with the prior art, the present invention has highly ordered macroporous and mesoporous structures, which can greatly enhance the gas adsorption efficiency and make the catalytic reaction more efficient;
[0129] Future application prospects: The present invention has broad application prospects, especially in the field of exhaust gas post-treatment. By introducing polymer pore templates in steps, a highly ordered pore structure with different pore sizes is formed in the cerium-based catalyst, which significantly improves the performance of the catalyst. With the further implementation of the "dual carbon" policy, the requirements for exhaust gas post-treatment are further improved. The present invention is expected to play a greater role in the field of mobile source post-treatment.
[0130] The specific embodiments described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A method for preparing a catalyst material based on a sol-gel method, characterized in that: The method comprises the following steps: S10, dissolving methyl methacrylate in deionized water under an inert gas to obtain a methyl methacrylate solution; S20, using the persulfate solution as an initiator to undergo a polymerization reaction with the methyl methacrylate solution to obtain a polymethyl methacrylate microsphere mother solution; S30, diluting, centrifuging and drying the polymethyl methacrylate microsphere mother solution to obtain a polymethyl methacrylate template; S40, dissolving deionized water and polyethylene oxide-polypropylene oxide-polyethylene oxide in anhydrous ethanol, stirring and mixing, and then adding cerium salt to obtain solution A; S50, adding glacial acetic acid to the titanate, and mixing by stirring to obtain a solution B; S60, adjusting the pH of solution A, and adding solution B dropwise to solution A, and mixing by stirring to obtain gel C; S70, heat-treating the polymethyl methacrylate template, and dropping the gel C on the polymethyl methacrylate template, and obtaining a catalyst material by vacuum filtration, drying and calcining.
2. The method for preparing a catalyst material based on a sol-gel method according to claim 1, characterized in that: The step of dissolving methyl methacrylate in deionized water under an inert gas to obtain a methyl methacrylate solution comprises the following steps: S101, introducing an inert gas into a four-necked flask filled with deionized water; S102, placing the four-necked flask in an oil bath for heating and stirring; S103, adding methyl methacrylate into evenly stirred deionized water, and dissolving by stirring to obtain a methyl methacrylate solution.
3. The method for preparing a catalyst material based on a sol-gel method according to claim 2, characterized in that: The method of using the persulfate solution as an initiator and polymerizing it with the methyl methacrylate solution to obtain the polymethyl methacrylate microsphere mother solution comprises the following steps: S201, dissolving persulfate in deionized water, stirring and mixing to obtain a persulfate solution, and using the solution as an initiator; S202, adding an initiator to the methyl methacrylate solution to obtain a polymethyl methacrylate microsphere mother solution through a polymerization reaction.
4. The method for preparing a catalyst material based on a sol-gel method according to claim 3, characterized in that: The persulfate includes at least one of ammonium persulfate, sodium persulfate and potassium persulfate.
5. The method for preparing a catalyst material based on a sol-gel method according to claim 1, characterized in that: The step of diluting, centrifuging and drying the polymethyl methacrylate microsphere mother solution to obtain the polymethyl methacrylate template comprises the following steps: S301, adding the polymethyl methacrylate microsphere mother solution into deionized water according to a preset volume ratio for dilution treatment; S302, centrifugally filtering the diluted polymethyl methacrylate microsphere mother solution; S303, placing the polymethyl methacrylate microsphere mother liquid after the centrifugal filtration treatment in an oven for drying treatment to obtain a polymethyl methacrylate template with a blue luster.
6. The method for preparing a catalyst material based on a sol-gel method according to claim 1, characterized in that: The step of dissolving deionized water and polyethylene oxide-polypropylene oxide-polyethylene oxide in anhydrous ethanol, stirring and mixing, and then adding cerium salt to obtain solution A comprises the following steps: S401, uniformly mixing deionized water and polyethylene oxide-polypropylene oxide-polyethylene oxide according to a preset mass ratio to obtain a mixed reagent; S402, adding the mixed reagent to anhydrous ethanol and performing magnetic stirring under heating in a water bath until the polyethylene oxide-polypropylene oxide-polyethylene oxide is dissolved to obtain a dissolved solution; S403, adding cerium salt to the dissolved solution and mixing by stirring to obtain solution A.
7. The method for preparing a catalyst material based on a sol-gel method according to claim 6, characterized in that: The cerium salt includes at least one of cerium nitrate, cerium chloride, cerium sulfate and cerium acetate.
8. The method for preparing a catalyst material based on a sol-gel method according to claim 1, characterized in that: The titanate includes at least one of tetrabutyl titanate, tetraethyl titanate and tetraisopropyl titanate.
9. The method for preparing a catalyst material based on a sol-gel method according to claim 1, characterized in that: The step of adjusting the pH of solution A, adding solution B dropwise to solution A, and stirring to obtain gel C comprises the following steps: S601, adding nitric acid dropwise to solution A to adjust the pH of solution A to a range of 1-2; S602, adding solution B dropwise to solution A with adjusted pH, and mixing by stirring to obtain gel C.
10. The method for preparing a catalyst material based on a sol-gel method according to claim 1, characterized in that: The step of heat treating the polymethyl methacrylate template, dripping the gel C onto the polymethyl methacrylate template, vacuum filtering, drying and calcining to obtain the catalyst material comprises the following steps: S701, adding gel C dropwise to the heat-treated polymethyl methacrylate template; and performing vacuum filtration treatment; S702, performing vacuum filtration and preliminary drying treatment on the polymethyl methacrylate template after the gel C is added; S703, performing secondary drying on the polymethyl methacrylate template that has been subjected to several vacuum filtration and preliminary drying treatments; S704, sending the polymethyl methacrylate template after secondary drying into a muffle furnace for calcination to obtain a catalyst material.
Citation Information
Patent Citations
Preparation method of doped CeO2-TiO2 catalyst
CN105664910A
Three-dimensional ordered macroporous structure (3DOM)-manganese cerium titanium composite oxide denitration catalyst and preparation method thereof
CN113198460A
Preparation method and application of L acid catalyst for producing methyl methacrylate
CN115364889A
Preparation method and application of catalyst for eliminating soot particles of diesel vehicle
CN116510720A
Titanium dioxide powder for honeycomb exhaust gas treatment catalyst and honeycomb exhaust gas treatment catalyst using the titanium dioxide powder
JP2004000943A